Computer-Aided Freehand Maxillary Repositioning. Issue 1 (January 2018) - Lin, Xiaozhen; Sun, Yi; Han, Xiaodong; Wang, Jing; Zhang, Ming; Liang, Limin
Abstract : Abstract: The authors aimed to test the hypothesis that in orthognathic surgery the maxilla could be repositioned using spatial distances from Glabella to 3 maxillary dental landmarks as references. An asymmetric skeletal Class 3 malocclusion patient was involved and bimaxillary orthognathic surgery was planned. Virtual surgery was simulated and spatial distances from Glabella to midpoint of the upper dentition (U0) and bilateral medial-buccal cusp of the first molar (6L and 6R) were measured. These distances were used as the repositioning references and were imported intraoperatively into a digital caliper after the maxilla was mobilized, the repositioning of maxilla was manipulated till all the true spatial distances reached the references. Postoperative computed tomography head model were superimposed onto the planned head model, the maxillary repositioning error was assessed using spatial distances between the pre- and postoperative dental landmarks. The asymmetric skeletal Class 3 malocclusion was corrected through bimaxillary surgery and the errors at U0, 6R and 6L was 1.37, 1.79, and 1.45 mm. The maxilla could be repositioned using spatial distances from Glabella to 3 maxillary dental landmarks as references.